The Influence of Internal Control Implementation and Managerial Performance On Financial Accountability Local Government in Indonesia - Kewo, Cecilia Lelly (International Journal of Economics and Financial Issues, 2017)
The purpose of this study to examine whether the financial accountability is affected by the internal control and managerial performance of local government in Indonesia. Usefulness of research as input for the government to improve internal control, managerial performance and financial accountability. Population in this study all local government unit of North Sulawesi province are 226 unit tool (SKPD).Number of samples 115 unit tool with respondents as many as 345 civil servants. Data collection using primary data. Method data testing conducted by validity and reliability. With Structural Equation Model (SEM) approach Partial Least Square (PLS), confidence level 95% and Î± 0.05, the hypothesis was rejected H0. The conclusion is implementation of internal control influence on financial accountability. Managerial performance influence on financial accountability in local government in Indonesia. Keywords: internal control, managerial performance, financial accountability JEL Classifications: M4, H7, G3